Microbiological quality Assessment of hospital food in a public hospital in Fez (Morocco) - Zbadi, L.; El Ouali Lalami, A.; Baroudi, A.; Marsou, Z.; Benbrahim, K. Fikri (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The food safety has become a major issue in hospitals, since patients are especially vulnerable to foodborne illness considered as nosocomial infection. Aims: To assess health hazards in food at a hospital in Fez city (Morocco). Material and Results: Hygienic quality of food samples (n = 81: meals (40%), plants and vegetables (35%); meat / meat products (17%)) and contact surfaces (n = 80: local (32,5;%), equipment (50%) and staffs hands (17,5%)) was evaluated during 2011, and involved germs have been researched using standard methods. Results interpreted according to the Moroccan and French standards showed that the percentage of foods non-compliance was 12%, with 32% for plants / vegetables and 7% for meat / meat products. The criminalization of fecal coliform was the important (91%) compared with Staphylococcus aureus (9%). Salmonella sp., Listeria monocytogenes, anaerobic sulphito-reducers, yeasts and molds were not implicated. Contact surfaces analysis showed that 40% of equipment, 38% of local and 29 % of the staffs hands were not clean. The causative organisms were fecal coliforms (60%) and S. aureus (40 %). Conclusion: Contact surfaces may affect the hygienic quality of food served in the hospital. That could make the warning signal in hospitals for the establishment of a global quality policy to ensure food safety and to prevent healthcare associated infections.